Why should we strive to let them thrive? Exploring the links between homecare professionals thriving at work, employee ambidexterity, and innovative behavior - Terje Slåtten; Barbara Rebecca Mutonyi; Gudbrand Lien (BMC Health Services Research)
Abstract Background The concept of thriving at work (TAW) has received increased interest within health services research in recent years. TAW embraces employees’ experience of being energized and feeling alive when employed in an organization. However, previous research has been limited mainly to the investigation of factors that promote TAW. Consequently, there is a lack of research linking TAW to potential outcomes. Based on this knowledge gap, this study aimed to examine links between TAW and two potential outcomes: employees’ individual innovative behavior (IIB) and employee ambidexterity (EA). Thus, the study contributes to a relatively neglected area, homecare, within the domain of health services research. Methods In this cross-sectional study, N = 258 Norwegian homecare professionals in nine municipalities were selected through convenience sampling. The conceptual model's results were analyzed using partial least-squares structural equation modeling with SmartPLS 3 software. The study tested both direct and indirect relationships. Indirect relationships were achieved through bootstrap. Results The main results from the empirical study can be summarized as follows: (i) TAW was found to be positively linked to both EA (b = 0.46) and IIB (b = 0.22); (ii) TAW and EA explained about 30% (R2 = 0.29) the variance in IIB; (iii) The relationship between TAW and IIB was found to be mediated by the EA; (iv) TAW was positively linked to each of the two dimensions that constitute EA. However, when comparing the individual strength of linkages, TAW was found to be most strongly linked to the exploitation dimension of EA (b = 0.50) and less strongly linked to the exploration dimension of EA (b = 0.35). Conclusions Employees’ level of TAW in homecare services is linked to desirable outcomes, as represented by EA and IIB in this study. Managers should be aware of the development and changes in their employees' TAW levels. Consequently, continuously monitoring and cultivating the TAW of individual employees to determine whether they experience a sense of being energized and feeling alive as members of the organization is an important practical implication. TAW is a key to essential outcomes. Managers should, therefore, strive to let all of their employees thrive.